Development of a novel ionic liquid–curcumin complex to enhance its solubility, stability, and activity. Issue 54 (11th June 2019) - Chowdhury, Md. Raihan; Moshikur, Rahman Md; Wakabayashi, Rie; Tahara, Yoshiro; Kamiya, Noriho; Moniruzzaman, Muhammad; Goto, Masahiro
Abstract : We report a one-step emulsification and rapid freeze-drying process to develop a curcumin–ionic liquid (CCM–IL) complex that could be readily dispersed in water with a significantly enhanced solubility and half-life compared to free CCM. Abstract : We report a one-step emulsification and rapid freeze-drying process to develop a curcumin–ionic liquid (CCM–IL) complex that could be readily dispersed in water with a significantly enhanced solubility of ∼8 mg mL −1 and half-life ( t 1/2 ) of ∼260 min compared with free CCM (solubility ∼30 nM and t 1/2 ∼ 20 min). This process using an IL consisting of a long chain carbon backbone as a surfactant, may provide an alternative way of enhancing the solubility of poorly water-soluble drugs.